Determination of Total Phenol Content and Evaluation of Antioxidant Activity of Paronychia Argentea L. Spread in the Syrian Coast and Determination of the Chemical Composition of its Essential Oil - الشماع, عصام; الصالح, جمانة; درويش, منال (Latakia University Journal -Medical Sciences Series, 2020)
Paronychia argentea L. of Caryophylleacea is one of the plants widely used in traditional medicine to cystitis treatment, prostate and diabetes because it is richness in chemical compounds. This research aims to determine the total content of phenols and assess the anti-oxidant capacity of plant spread in the Syrian coast, plant was extracted by maceration in three different solvents separately, anti-oxidant activity was estimated by scaving free radical DPPH. reagent, then the essential oil was extracted from the aerial parts of the plant, and analyzing by GC / MS technique. The aqueous extract showed the highest content of phenols, while the anti-oxidant ability was higher in the methanolic extract, and GC/ MS analysis recorded a group of compounds of which ten compounds were identified, the main compound was Caryophyllene at a percentage of 28.74%.